Dynamic coupling of fast channel gating with slow ATP-turnover underpins protein transport through the Sec translocon - Crossley, Joel A; Allen, William J; Watkins, Daniel W; Sabir, Tara; Radford, Sheena E; Tuma, Roman; Collinson, Ian; Fessl, Tomas (EMBO journal, 2024)
The Sec translocon is a highly conserved membrane assembly for polypeptide transport across, or into, lipid bilayers. In bacteria, secretion through the core channel complex-SecYEG in the inner membrane-is powered by the cytosolic ATPase SecA. Here, we use single-molecule fluorescence to interrogate the conformational state of SecYEG throughout the ATP hydrolysis cycle of SecA. We show that the SecYEG channel fluctuations between open and closed states are much faster (~20-fold during translocation) than ATP turnover, and that the nucleotide status of SecA modulates the rates of opening and closure. The SecY variant PrlA4, which exhibits faster transport but unaffected ATPase rates, increases the dwell time in the open state, facilitating pre-protein diffusion through the pore and thereby enhancing translocation efficiency. Thus, rapid SecYEG channel dynamics are allosterically coupled to SecA via modulation of the energy landscape, and play an integral part in protein transport. Loose coupling of ATP-turnover by SecA to the dynamic properties of SecYEG is compatible with a Brownian-rachet mechanism of translocation, rather than strict nucleotide-dependent interconversion between different static states of a power stroke.
Keywords: proteiny SecA; nukleotidy; bakteriální proteiny; translokační kanály SEC; SecA Proteins; Protein Transport; adenosintrifosfát; Adenosine Triphosphate; SEC Translocation Channels; proteiny z Escherichia coli; Nucleotides; Bacterial Proteins; adenosintrifosfatasy; transport proteinů; Escherichia coli Proteins; Adenosine Triphosphatases